AUDEN’S CRITIQUE OF MODERNITY: TECHNOLOGY, ALIENATION AND SOCIAL DISCONNECTION - Harsh, Siprah; Pandey, Mantosh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
W.H. Auden, one of the most influential poets of the 20th century, frequently addressed the complexities of modernity in his works. His poetry reveals a profound critique of how technological advancement, alienation, and social disconnection have shaped human experience. Auden’s writings often explore the tension between technological progress and the loss of personal intimacy and community. In poems like The Shield of Achilles and September 1, 1939, Auden presents a world where mechanical efficiency and scientific achievements come at the cost of moral decay and emotional isolation. He critiques the dehumanizing aspects of modernity, highlighting how the pursuit of technological innovation leads to a sense of estrangement from nature, tradition, and interpersonal relationships. This article examines how Auden’s treatment of modernity serves as a commentary on the ethical and social implications of technology, and how his poetry urges readers to reconsider the values that guide contemporary life.